Cytotoxic activity of Thai medicinal plants against human cholangiocarcinoma, laryngeal and hepatocarcinoma cells in vitro - Itharat Arunporn; Chaijaroenkul Wanna; Viyanant Vithoon; Mahavorasirikul Wiratchanee; Na-Bangchang Kesara (BMC, 2010)
Abstract Background Cholangiocarcinoma is a serious public health in Thailand with increasing incidence and mortality rates. The present study aimed to investigate cytotoxic activities of crude ethanol extracts of a total of 28 plants and 5 recipes used in Thai folklore medicine against human cholangiocarcinoma (CL-6), human laryngeal (Hep-2), and human hepatocarcinoma (HepG2) cell lines in vitro. Methods Cytotoxic activity of the plant extracts against the cancerous cell lines compared with normal cell line (renal epithelial cell: HRE) were assessed using MTT assay. 5-fluorouracil was used as a positive control. The IC50 (concentration that inhibits cell growth by 50%) and the selectivity index (SI) were calculated. Results The extracts from seven plant species (Atractylodes lancea, Kaempferia galangal, Zingiber officinal, Piper chaba, Mesua ferrea, Ligusticum sinense, Mimusops elengi) and one folklore recipe (Pra-Sa-Prao-Yhai) exhibited promising activity against the cholangiocarcinoma CL-6 cell line with survival of less than 50% at the concentration of 50 μg/ml. Among these, the extracts from the five plants and one recipe (Atractylodes lancea, Kaempferia galangal, Zingiber officinal, Piper chaba, Mesua ferrea, and Pra-Sa-Prao-Yhai recipe) showed potent cytotoxic activity with mean IC50 values of 24.09, 37.36, 34.26, 40.74, 48.23 and 44.12 μg/ml, respectively. All possessed high activity against Hep-2 cell with mean IC50 ranging from 18.93 to 32.40 μg/ml. In contrast, activity against the hepatoma cell HepG2 varied markedly; mean IC50 ranged from 9.67 to 115.47 μg/ml. The only promising extract was from Zingiber officinal (IC50 = 9.67 μg/ml). The sensitivity of all the four cells to 5-FU also varied according to cell types, particularly with CL-6 cell (IC50 = 757 micromolar). The extract from Atractylodes lancea appears to be both the most potent and most selective against cholangiocarcinoma (IC50 = 24.09 μg/ml, SI = 8.6). Conclusions The ethanolic extracts from five plants and one folklore recipe showed potent cytotoxic activity against CL-6 cell. Sensitivity to other cancerous cell lines varied according to cell types and the hepatocarcinoma cell line. HepG2 appears to be the most resistant to the tested extracts.